2016
DOI: 10.1111/obr.12407
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is an independent risk factor for non‐alcoholic fatty liver disease: evidence from a meta‐analysis of 21 cohort studies

Abstract: Obese individuals have a 3.5-fold increased risk of developing NAFLD, and there is an obvious dose-dependent relationship between BMI and NAFLD risk. © 2016 World Obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
211
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(235 citation statements)
references
References 72 publications
(135 reference statements)
11
211
1
12
Order By: Relevance
“…In prospective longitudinal studies, the presence of NAFLD has been associated with an increased risk of cardiovascular disease (CVD) and type 2 diabetes (T2DM); however, it remains unclear whether NAFLD is causally related to these conditions or, rather, it is just an epiphenomenon of other cardiometabolic factors causally related to CVD and T2DM . In fact, the rising prevalence of NAFLD concurs with that of overweight and obesity (particularly visceral fat) . Moreover, as excess body weight is also a risk factor for CVD and T2DM, it has been argued that the associations of NAFLD with CVD and T2DM could be spurious (ie, non‐causal) and reflect the link between overweight/obesity with CVD and T2DM .…”
Section: Introductionmentioning
confidence: 99%
“…In prospective longitudinal studies, the presence of NAFLD has been associated with an increased risk of cardiovascular disease (CVD) and type 2 diabetes (T2DM); however, it remains unclear whether NAFLD is causally related to these conditions or, rather, it is just an epiphenomenon of other cardiometabolic factors causally related to CVD and T2DM . In fact, the rising prevalence of NAFLD concurs with that of overweight and obesity (particularly visceral fat) . Moreover, as excess body weight is also a risk factor for CVD and T2DM, it has been argued that the associations of NAFLD with CVD and T2DM could be spurious (ie, non‐causal) and reflect the link between overweight/obesity with CVD and T2DM .…”
Section: Introductionmentioning
confidence: 99%
“…Cause and gender-specific data on relative risks (along with 95% Confidence Intervals) for 16 diagnoses were obtained from a Canadian cost of illness study based on meta-analyses [17] and from a more recent meta-analyses for type II diabetes [18], non-alcoholic fatty liver disease [19] and gout [20], the latter two diagnosis specific risks being based on average BMI levels of 27.3 and 33.6 in Israeli overweight and obese persons respectively [21]. …”
Section: Methodsmentioning
confidence: 99%
“…Obesity is closely associated with diabetes, nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH), and cardiovascular diseases (64). Numerous studies have reported that dysregulation of sphingolipid metabolism is linked to diabetes (4).…”
Section: Sphks and S1p In Lipid Metabolismmentioning
confidence: 99%